Isolation and Whole-genome Sequence Analysis of the Imipenem Heteroresistant Acinetobacter baumannii Clinical Isolate HRAB-85 - Puyuan Li; Yong Huang; Lan Yu; Yannan Liu; Wenkai Niu; Dayang Zou; Huiying Liu; Jing Zheng; Xiuyun Yin; Jing Yuan; Xin Yuan; Changqing Bai (International Journal of Infectious Diseases, 2017)
Objectives: Heteroresistance is a phenomenon in which there are various responses to antibiotics from bacterial cells within the same population. Here, we isolated and characterised an imipenem heteroresistant Acinetobacter baumannii strain (HRAB-85). Methods: The genome of strain HRAB-85 was completely sequenced and analysed to understand its antibiotic resistance mechanisms. Population analysis and multilocus sequence typing were performed. Results: Subpopulations grew in the presence of imipenem at concentrations of up to 64 μg/mL, and the strain was found to belong to ST208. The total length of strain HRAB-85 was 4,098,585 bp with a GC content of 39.98%. The genome harboured at least four insertion sequences: the common ISAba1, ISAba22, ISAba24, and newly reported ISAba26. Additionally, 19 antibiotic-resistance genes against eight classes of antimicrobial agents were found, and 11 genomic islands (GIs) were identified. Among them, GI3, GI10, and GI11 contained many ISs and antibiotic-resistance determinants. Conclusions: The existence of imipenem heteroresistant phenotypes in A. baumannii was substantiated in this hospital, and imipenem pressure, which could induce imipenem-heteroresistant subpopulations, may select for highly resistant strains. The complete genome sequencing and bioinformatics analysis of HRAB-85 could improve our understanding of the epidemiology and resistance mechanisms of carbapenem-heteroresistant A. baumannii.